Comparative evaluation of two toric intraocular lenses for correcting astigmatism in patients undergoing phacoemulsification - Seth, Sheetal A (Indian J Ophthalmol, 2018)
PURPOSE: To compare the efficacy of AT-TORBI plate haptic toric intraocular lens (IOL) (Carl Zeiss Meditec AG, Jena, Germany) and AcrySof loop haptic toric IOL (Alcon Laboratories, Inc., Fort Worth, TX, USA) for correcting preexisting astigmatism of ≥1 diopters (D) in patients undergoing phacoemulsification and to compare the rotational stability of these two toric IOLs. METHODS: In this prospective randomized controlled trial. Forty-two eyes of 42 cataract patients with preexisting astigmatism of 1 D or more were randomized to receive plate haptic toric (AT TORBI) or loop haptic toric (AcrySof) IOLs, with 21 in each group. Postoperative evaluation was done at day 1, 1 week, 1 month, and 3 months. Uncorrected distance visual acuity (UDVA), best corrected visual acuity (VA), and IOL position were noted in both the groups. RESULTS: At 3 months postoperatively, the mean log MAR UDVA was 0.23 ± 0.20 and 0.20 ± 0.13 in Groups I and II, respectively (P = 0.7), the mean residual cylindrical refractive error in plate haptic toric group was 0.40 ± 0.31 D and in loop haptic group was 0.45 ± 0.33 D (P = 0.64). The mean IOL rotation at 3 months follow-up in plate haptic group was found to be 3.52 ± 3.84° and in loop haptic group was 2.05 ± 2.56° (P = 0.25). CONCLUSION: Both types of toric IOLs were equally efficacious for attaining good uncorrected VA and correcting preexisting astigmatism between 1–5 D. Both of them were rotationally stable at 3 months follow-up.